2012
DOI: 10.1007/s10897-012-9524-8
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic Counseling and Testing for FMR1 Gene Mutations: Practice Guidelines of the National Society of Genetic Counselors

Abstract: PURPOSE Fragile X syndrome (FXS) is one of several clinical disorders associated with mutations in the Xlinked Fragile X Mental Retardation-1 (FMR1) gene. With evolving knowledge about the phenotypic consequences of FMR1 transcription and translation, sharp clinical distinctions between pre-and full mutations have become more fluid. The complexity of the issues surrounding genetic testing and management of FMR1-associated disorders has increased; and several aspects of genetic counseling for FMR1 mutations rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
74
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 44 publications
(45 reference statements)
0
74
0
3
Order By: Relevance
“…Participants were unanimous in their views that individuals with test-positive results arising from FXS carrier screening should be provided with genetic counseling which is consistent with current recommendations (Finucane et al 2012;McConkie-Rosell et al 2007). Research indicates that individuals identified as carriers through population screening may differ in their genetic counseling needs compared with individuals who have a personal or family history of FXS, as they may be relatively unprepared for a carrier result (Anido et al 2005(Anido et al , 2007 and may have very limited knowledge and prior experience of FXS (Archibald et al 2009).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Participants were unanimous in their views that individuals with test-positive results arising from FXS carrier screening should be provided with genetic counseling which is consistent with current recommendations (Finucane et al 2012;McConkie-Rosell et al 2007). Research indicates that individuals identified as carriers through population screening may differ in their genetic counseling needs compared with individuals who have a personal or family history of FXS, as they may be relatively unprepared for a carrier result (Anido et al 2005(Anido et al , 2007 and may have very limited knowledge and prior experience of FXS (Archibald et al 2009).…”
Section: Discussionmentioning
confidence: 72%
“…Recommendations from the American College of Obstetricians and Gynecologists (2010) suggest that carrier screening be offered to women without a family history of FXS if it is requested. The need for appropriate education and genetic counseling has been emphasized as has the importance of research exploring psychosocial impacts of such screening (Finucane et al 2012;Sherman et al 2005). Research indicates that population screening for FXS is generally perceived favorably by families and healthcare providers (Acharya and Ross 2009;Archibald et al 2013;Ryynanen et al 1999;Skinner et al 2003) as well as individuals offered screening in research contexts (Anido et al 2005(Anido et al , 2007Archibald et al 2009;Fanos et al 2006;Metcalfe et al 2008;Sherman et al 2005), and there appears to be a preference for screening offered before pregnancy (Acharya and Ross 2009;Archibald et al 2013;Skinner et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Emotional and psychiatric problems are common, even among those with normal intelligence. 43 Premutation carriers are at risk for 2 late-onset health conditions, fragile X-associated tremor/ataxia syndrome and fragile X premature ovarian insufficiency. Fragile X-associated tremor/ataxia syndrome is characterized by intention tremor, cerebellar ataxia, atypical parkinsonism, and dementia.…”
Section: Fragile X Syndrome Empirical Datamentioning
confidence: 99%
“…This case demonstrates the importance of considering molecular genetic evaluation of FMR1 in the workup for secondary amenorrhea (1 ). Full mutations of FMR1 represent the most common inherited form of cognitive impairment, and premutations of FMR1 represent the most common inherited cause of POI.…”
mentioning
confidence: 91%